Survey of coat and reproductive age of quarter horses used in vaquejada in northeast micro-regions of Brazil - Bastos, Marisa Silva; Rezende, Marcos Paulo Gonçalves; Souza, Julio Cesar; Leite, Maybe Carneiro Paula; Figueiredo, Gabriel Chaves (Scientia Agraria Paranaensis, 2017)
<span style="font-size: 10pt; font-family: ’Helvetica’,sans-serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;" lang="EN-US">This study aimed to evaluate the coat and ages of Quarter Horse stallions used in equine production for Vaquejada in micro regions of the Northeast of Brazil. We used information from 264 horses, taken from the database of the Brazilian Association of Quarter Horse Breeders (ABQM). Were collected individual information: date of birth, sex and animal fur, number of copies of disputed official Vaquejada, better and worse placed, cumulative score in ABQM, coats and dates of parent’s birth (31), coats and birth dates of mothers (257). There was a higher frequency (P < 0.05) of births between the months of September and October. There was no age-specific greater use of stallions or matrix in reproduction (P > 0.05). There was no correlation (P > 0.05) between the number of children and the stallion beginning age at reproduction. There was a greater preference for coats sorrel (20.08%) and palomino (21.97%) in the progeny; the stallions were 34.47% palomino and 29.92% brown; while the matrices were 41.29% sorrel and 23.48% brown. Stallions palomino survived longer playback and more offspring. However, it was observed that while 93 of the 264 animals are children of at least one parent with bay coat or palomino, only 52 animals showed that the coat. It is concluded that the coat of stallions is related to greater frequency of use in reproduction; however, to obtain a coat expected in the progeny, we need to carry out a genetic study and not only phenotypic.